Moral Education in QS. Al-Baqarah:186 through Emilio Betti’s Hermeneutics: Responding to Contemporary Ethical Challenges - Nur Hakim; Tri Wahyu Hidayati (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
The moral decline in the modern era presents a serious challenge to Islamic education, particularly in shaping strong spiritual character towards Allah SWT. Qur’anic verse QS. Al-Baqarah:186 conveys the message of divine closeness that holds deep relevance for moral development. This study aims to analyze the verse using Emilio Betti’s hermeneutic approach to uncover the moral education dimension from historical, linguistic, and contextual perspectives. The research applies a qualitative-descriptive method through textual and philosophical-hermeneutic analysis. The findings reveal that the verse contains not only theological meaning but also universal ethical messages such as spiritual optimism and slot thailand obedience to divine commands. Through Betti’s approach, the study finds that the objective meaning structure of the verse is both transhistorical and contextual. This research offers a synthesis between classical Qur’anic exegesis and modern hermeneutics, contributing practical insights for developing Islamic moral education curricula that are integrative and responsive to contemporary moral challenges.